Organizing America: Wealth, Power, and the Origins of Corporate Capitalismby PerrowCharles. Princeton, NJ: Princeton University Press, 2002. - Stablein, Ralph (Academy of Management Review, 2003)
The article reviews the book ?Organizing America: Wealth, Power and the Origins of Corporate Capitalism,? by Charles Perrow.